Vexed on a Visit (A Lacey Doyle Cozy Mystery-Book 4) - Fiona, Grace (Lukeman Literary, 2020)
"Very entertaining. I highly recommend this book to the permanent library of any reader that appreciates a very well written mystery, with some twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews, Roberto Mattos (regarding Murder in the Manor) VEXED ON A VISIT (A LACEY DOYLE COZY MYSTERY-BOOK 4) is book four in a charming new cozy mystery series by Fiona Grace. Lacey Doyle, 39 years old and freshly divorced, has made a drastic change: she has walked away from the fast life of New York City and settled down in the quaint English seaside town of Wilfordshire. Summer has arrived, and Lacey is delighted when her chef boyfriend surprises her with an offer for a long weekend trip, a romantic getaway into the neighboring seaside towns of the British countryside, with her beloved dog, and a chance to go antiquing. But Lacey is even more surprised when her family shows up from New York on a surprise visit-and when they want to come along! Even worse, Lacey, in a neighboring town, finds herself in the midst of a murder scene. And once again, with her reputation on the line, she may be the only one who can solve it. Book #5 in the series will be available soon!
Keywords: Krimi, detektivky